Parent–Offspring Resemblance for Drinking Behaviors in a Longitudinal Twin Sample - Saunders, Gretchen R. B. (J Stud Alcohol Drugs, 2017)
OBJECTIVE: The purpose of the current study was to evaluate parent–offspring resemblance for alcohol consumption and dependence symptoms, including sex-specific effects, and how these patterns change across adolescence and early adulthood. METHOD: Three cohorts of twins were assessed longitudinally at five time points between ages 14 and 29 years, with parents directly assessed at intake, using structured interviews. Twin offspring and parents from the population-based Minnesota Twin Family Study were included for a total sample size of 3,762 offspring (52% female) and their parents. Alcohol use was measured using an index based on drinking quantity, frequency, maximum drinks, and number of intoxications. Alcohol dependence symptom counts were also used. RESULTS: Parent–offspring correlations for alcohol consumption increased from age 14 (r = .12) to age 17 (r = .25), remained stable from ages 17 through 24, and then decreased slightly by age 29 (r = .19). Familial resemblance for symptoms of alcohol dependence peaked at age 17 (r = .18) then decreased through age 29 (r = .11). Parent–offspring correlations of both measures did not vary significantly by sex of offspring or sex of parent. CONCLUSIONS: Overall, parent–offspring resemblance for alcohol use and problems is relatively stable after early adulthood, with resemblance for alcohol use at higher magnitudes across offspring development. Evidence for differential resemblance based on sex of offspring or parents was lacking.